Establishment of a novel triage system for SARS-CoV-2 among trauma victims in trauma centers with limited facilities. Issue 1 (16th June 2021) - Abdolrahimzadeh Fard, Hossein; Borazjani, Roham; Sabetian, Golnar; Shayan, Zahra; Boland Parvaz, Shahram; Abbassi, Hamid Reza; Aminnia, Shiva; Salimi, Maryam; Paydar, Shahram; Taheri Akerdi, Ali; Zare, Masome; Shayan, Leila; et al.
Abstract : Objectives: The triage of trauma patients with potential COVID-19 remains a major challenge given that a significant number of patients may be asymptomatic or pre-symptomatic. This study aimed to compare the specificity and sensitivity of available triage systems for COVID-19 among trauma patients. Furthermore, it aimed to develop a novel triage system for SARS-CoV-2 detection among trauma patients in centers with limited resources. Methods: All patients referred to our center from February to May 2020 were enrolled in this prospective study. We evaluated the SARS-CoV-2 triage protocols from the WHO, the Iranian Ministry of Health and Medical Education (MOHME), and the European Centre for Disease Control and Prevention (ECDC) for their effectiveness in finding COVID-19 infected individuals among trauma patients. We then used these data to design a stepwise triage protocol to detect COVID-19 positive patients among trauma patients. Results: According to our findings, the WHO protocol showed 100% specificity and 13.3% sensitivity. The MOHME protocol had 99% specificity and 23.3% sensitivity. While the ECDC protocol showed 93.3% sensitivity and 89.5% specificity, it did not prioritize patients based on traumatic injuries and unstable conditions. Our stepwise triage protocol, which prioritizes traumatic injuries, had 93.3% sensitivity and 90.3% specificity. Conclusion: Our study shows that the triage protocols from the WHO, MOHME and ECDC are not best equipped to diagnose SARS-CoV-2 infected individuals among trauma patients. In our proposed stepwise triage system, patients are triaged according to their hemodynamic conditions, COVID-19 related clinical states, and COVID-19 related laboratory findings. Our triage model can lead to more accurate and resource-effective management of trauma patients with potential COVID-19 infection. Level of evidence: Level Ⅲ.